Evaluasi Aktivitas Farmakologi Simplisia Kopi Arabika (Coffea arabica) pada Berbagai Konsentrasi terhadap Sistem Saraf Otonom dan Sistem Saraf Pusat - Anggun Aldiansa; Ilmi Nurashiilah; Nahla Aulia Azis; Nasifa Kayla Putri; Andi Tenriani Awaliyah; Ayu Azkiya; Aulya Nurul Imama R; Hilda Kadir; Muhammad Chairul Anam; Andi Utari Prasetya Ningrum (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Arabica coffee (Coffea arabica) contains various bioactive compounds such as caffeine, polyphenols, flavonoids, and alkaloids that have the potential to produce diverse pharmacological effects on both the autonomic and central nervous systems. The variation in its chemical composition is influenced by factors such as cultivar, post-harvest processing, and preparation methods, resulting in biological responses that are dose-dependent and not always linear. This study aimed to evaluate the pharmacological activity of arabica coffee simplicia powder at three concentrations (1%, 2%, and 4%) by observing parasympathomimetic, parasympatholytic, sympathomimetic, sympatholytic, analeptic, central nervous system stimulation and depression, as well as muscle relaxation parameters. The research was conducted using a laboratory experimental design with test animals administered orally according to the designated concentrations. The results showed that some parameters increased at higher concentrations, such as parasympathomimetic activity (51.85%) and central nervous system stimulation (63.74%), while other parameters demonstrated decreasing or biphasic patterns, such as sympatholytic activity, which was high at 1% and 4% but low at 2%, and analeptic activity, which dropped sharply at 2% and increased again at 4%. These response patterns align with literature indicating that caffeine and polyphenols such as chlorogenic acid may interact synergistically or antagonistically, generating complex pharmacological effects through mechanisms involving adenosine modulation, excitatory neurotransmitters, the enteric nervous system, as well as antioxidant and anti-inflammatory pathways. Overall, this study demonstrates that arabica coffee simplicia exhibits multipotential pharmacological activity, with responses strongly influenced by concentration and the composition of its bioactive compounds, thereby providing a basis for further research on the phytopharmaceutical potential of arabica coffee.